Modelling heterogeneous photocatalytic oxidation using suspended TiO2 in a photoreactor working in continuous mode: Application to dynamic irradiation conditions simulating typical days in July and February. (1st October 2020) - Plantard, Gael; Dezani, Chloé; Ribeiro, Enrique; Reoyo‐Prats, Brice; Goetz, Vincent
Abstract: Compared to more conventional techniques, advanced oxidation processes (AOP) hold significant promise in terms of elimination of organic (especially persistent) compounds and microorganisms (disinfection) in wastewater. If the objective is to power these processes using solar energy, we need to be able to manage the intermittency in the solar resource. This is an essential step for design and to ensure efficient operation of the treatment processes. As solar radiation is inherently variable due to day/night cycles, seasonal cycles, and weather meteorological conditions, solar AOP performances are difficult to establish using conventional measures. To address this gap, we carry out experimental campaigns under controlled conditions and develop modelling tools capable of describing dynamic‐mode photocatalytic degradation. Here we develop a way to capture the responses of a photoreactor subjected to various stresses, including irradiation conditions, via an LED panel. Using a model that considers the influence of UV flux density and pollutant concentration made, it was possible to represent photoreactor responses under different irradiation conditions and feeds (concentration or flow at the input). The ultimate objective is to study the photocatalytic capacity of the photoreactor under irradiation conditions simulating a real day of sunshine. Abstract : Example of the evolution of MO concentration in a photoreactor (○) submitted to sunshine conditions in February (‐).